الطائفة اليهودية ودورها في إسقاط الدولة الجزائرية (1789 – 1830م) - حمية، يمينة, شوشاني عبيدي، الزهرة (جامعة الوادي university of Eloued, 2020)
الملخص: يعود التواجد اليهودي بالجزائر الى فترة ما قبل الميلاد وهناك من يقول ان تواجدهم سبق تواجد الرومان، حيث يقدرون أن أول دفعة منهم وصلت الى شمال إفريقيا مع مجيء الفينيقيين الذين أسسوا قرطاج، وأواسط القرن الثامن قبل الميلاد وبعد الفتح الإسلامي، ويقال أيضا ان تدفق اليهود على الجزائر استمر الى غاية استقلال الجزائر سنة 1962. حيث انقسموا الى ثلاثة اقسام: أولهم: يهود التوشابين أو اليهود الأهالي، وهم من جاءوا عند الهجرات الفينيقية، أما القسم الثاني هم يهود الميغروشيم أو اليهود الاندلسيون، وهم من جاءوا من الأندلس، واما عن الصنف الثالث وهم يهود ليفورن او اليهود الفرنسيين، فقد قدموا من مدينة ليفورنة في القرن السابع عشر ميلادي، وكانوا يلقبون بيهود النصارى. وقد اجمع اغلب المؤرخين عن أن هذه الطّائفة (يهود ليفورن) لعبة دور مهم في تحديد مصير الجزائر العثمانية، عندما سُمِحَ لهم بإنشاء مخازم العبيد والبضاعة. فقد نشأة بينهم وبين يهود الجزائر الأصليين علاقة مستمرة كوسطاء تجاريين ثم استقر يهود ليفورن بالجزائر نهائيا منذ 1723م، ليُكَوِّنوا ثروة طائلة لهم لِيُوَرّطوا البلاد في الاحتلال وذلك من خلال سيطرتهم على مقاليد التجارة الداخلية والخارجية بواسطة شركة بكري وبوشناق دون ان ننسى تحكم اليهود وتغلغلهم في الوسائط الحكومية وتشجيع الحكام لهم، كل هذا أدى الى ضعف الدولة الجزائرية وإسقاطها. Summary:إنجليزية The Jewish presence in Algeria dates back to the bc period and there are those who say that their presence has already beenThe Romans, who appreciated that the first batch of them arrived in North Africa with the arrival of the Phoenicians who founded Carthage, the middle of the eighth century BC and after the Islamic conquest, it is also said that the flow ofThe Jews of Algeria continued until Algeria's independence in 1962. They were divided into three sections: the Toussaint Jews or native Jews, who came at the time of the Phoenician migrations, the second section was the Migrosheim Jews or the Andalusian Jews, who came from Andalusia, and the third class, the Jews of Livorn or the French Jews, came from the city of Livorne in the 17th century, and they were called The Jews of the Christians. Most historians have agreed that this community (The Jews of Livorn) played an important role in determining the fate of Ottoman Algeria, when they were allowed to set up slave stores and goods.They established a continuing relationship with the Jews of Algeria as commercial intermediaries, and the Jews of Livorn settled in Algeria permanently since 1723, to make a great fortune for them to bring the country into occupation through their control over the reins of internal and foreign trade by Bakri and BouchnakCompany.Without forgetting the control of the Jews and their penetration into the government media and the encouragement of the rulers to them, all this led to the weakness and overthrow of the Algerian state.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: اليهود في الجزائر; Juifs en Algérie; Jews in Algeria